Public stockholding programs: What options for a permanent solution? - Díaz-Bonilla, Eugenio (2017)
The use of public food stocks for food security purposes is a hotly debated topic in agricultural negotiations within the World Trade Organization (WTO) (see Díaz-Bonilla, 2014, 2017a and 2017b). That debate needs to consider both the legal standing of public food stocks under the WTO framework, but, also, the more substantive issue of whether those instruments make sense in economic terms, particularly whether they are the best option to achieve food security. In this chapter I discuss briefly both aspects, starting with the economic considerations and then moving on to legal issues (a more detailed discussion of both topics can be found in Díaz-Bonilla, 2013, 2014, 2017a and 2017b).